COMPARING FODDER PRODUCTION OF MAIZE VARIETIES UNDER VARIED NITROGEN LEVELS - Haseeb AHMAD; Uzair AHMED; Ikram ULLAH; Hamza MASUD (Journal of Applied Life Sciences and Environment)
Maize (Zea mays L.) plays a significant role as a fodder crop, supporting rural populations and livestock. Unfortunately, in Pakistan, there is a shortage of green fodder due to the unbalanced use of fertiliser and improper selection of maize varieties for fodder production. This research aimed to address the need for quality fodder by studying the effects of nitrogen (N) on new maize varieties, ultimately enhancing livestock production and agricultural sustainability. The experiment took place in the summer of 2022 at the Cereal Crop Research Institute in Pakistan. Adopting an RCB design with three replications, fodder maize varieties (Jalal, Kaptan and Jumbo) were tested with four N levels (0, 100, 150, 200 kg N ha−1) applied during sowing, knee (V4), and silking stages. The data upon analysis revealed that different maize varieties had a significant impact on the studied parameters. Maize varieties affected days to tasselling and silking, with the Jumbo variety recording the longest duration (59 and 62, respectively). Similar results were observed for days to milking, with the Jumbo variety taking the longest time (80 days). It also recorded a higher leaf number (11.5), leaf area (478 cm−2) and leaf area index (3.4). Fresh fodder (67,777 kg ha−1) and dry fodder yield (23,424 kg ha−1) were higher for the Jumbo variety. In terms of N application, tasselling (59) and silking (62) took more days when 150 and 200 kg N ha−1 was applied compared to the control. Compared to the control plots (83 days), 200 kg N delayed the milking stage by 10 days. A higher but statistically similar leaf count, leaf area and leaf area index were recorded with 150 and 200 kg N ha−1. The plant height of maize was also higher, with 150 (196 cm) and 200 kg N ha−1 (202 cm). Lastly, a higher fresh fodder and dry fodder yield was associated with 150 and 200 kg N ha−1. Based on these results, the Jumbo variety, with the application of 150 kg N ha−1, is recommended for cultivation for economic feasibility and to obtain a higher fodder yield of maize.